Perspectives in nanoscience and nanotechnology - Moreno-Mosquera, Asdrubal; Alvarez-Polo, Yolima (Visión electrónica, 2021)
This work is focused on reviewing the theoretical vision of the physicist Richard Feynman about nanoscience and nanotechnology, giving continuity to his ideas in the proper context of physics laws that has led nanoscience and nanotechnology to become robust and active sciences. Some implications of nanotechnology as a general-purpose foundational technology for all economic areas are discussed. Some aspects related to interactions between the fields of mathematics, high-energy physics and condensed matter physics that have allowed the remarkable development of new quantum material platforms for nanoelectronics are also analyzed.